1970
DOI: 10.1063/1.1672953
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Chloride Vibrational Populations Produced by the H and D Atom Reactions with SCl2 and S2Cl2

Abstract: Infrared emission intensities from HCl and DCl products in high vibrational levels have been used to measure energy partitioning in the reactions of H and D atoms with SCl2 and S2Cl2. The results are compared to the infrared chemiluminescence from the H and D atom reactions with Cl2. The relative vibrational level populations were measured under experimental conditions such that vibrational relaxation was minimized. The H atom reactions with SCl2 and S2Cl2 partitioned >37% and >36% of the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1971
1971
1983
1983

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…One can see from N,=z/N'=l that our vibrational distribution (Table 2) is less relaxed than the distribution of Setser and coworkers [3J evaluated using the measured relaxation technique. Setser and his collaborators also attempted to correct for relaxation effects in their "comparative technique" using the known relaxation behaviour of HCl formed by the reaction H + Clz' This procedure is doubtful because of the different deactivation probabilities for Cl, and SzCl z [3,14].…”
Section: The Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…One can see from N,=z/N'=l that our vibrational distribution (Table 2) is less relaxed than the distribution of Setser and coworkers [3J evaluated using the measured relaxation technique. Setser and his collaborators also attempted to correct for relaxation effects in their "comparative technique" using the known relaxation behaviour of HCl formed by the reaction H + Clz' This procedure is doubtful because of the different deactivation probabilities for Cl, and SzCl z [3,14].…”
Section: The Reagentsmentioning
confidence: 99%
“…Early measured relaxation studies by Johnson et al [3] showed the presence of excited HCI molecules. The first rotational distribution for this reaction was reported by Heydtmann and Polanyi [4].…”
Section: The Reaction H + Sclmentioning
confidence: 99%
See 1 more Smart Citation